Pengaruh Bauran Pemasaran 5P Terhadap Kepuasan Pelanggan Grosir Gotong Royong Jaya Jember - Budi iwantoro; Muhaimin Dimyati; Haifah Dimyati (CV. ITTC INDONESIA, 2025)
This study aims to determine and analyze the effect of price, service quality, product diversity, word of mouth and store atmosphere on customer satisfaction at the Gotong Royong Jaya Jember wholesale store. The problems studied include whether each of these independent variables has a partial or simultaneous effect on customer satisfaction. This research uses a quantitative approach with survey methods and explanatory design. Data were collected through distributing questionnaires to 60 respondents who had visited at least once to the Gotong Royong Jaya Wholesale Store, with purposive sampling technique. The research instrument used a Likert scale and the data was analyzed using multiple linear regression with the help of SPSS. The results showed that the variables of price, service quality, product diversity, word of mouth and store atmosphere simultaneously had a significant effect on customer satisfaction. Partially, service quality and store atmosphere have the most dominant influence. These findings confirm the importance of a comfortable consumer experience-based marketing strategy in increasing customer satisfaction and loyalty in the wholesale industry